Does robotization affect job quality? Evidence from European regional labour markets - José Ignacio Antón Pérez; Enrique Fernández-Macías; Rudolf Winter-Ebmer (European Commission, Joint Research Centre (JRC), 2021)
Whereas there are recent papers on the effect of robot adoption on employment and wages, there is no evidence on how robots affect non-monetary working conditions. We explore the impact of robot adoption on several domains of non-monetary working conditions in Europe over the period 1995-2005 combining information from the World Robotics Survey and the European Working Conditions Survey. In order to deal with the possible endogeneity of robot deployment, we employ an instrumental variables strategy, using the robot exposure by sector in other developed countries as an instrument. Our results indicate that robotization has a negative impact on the quality of work in the dimension of work intensity and no relevant impact on the domains of physical environment or skills and discretion.
Keywords: 330; Robotization; Working conditions; Job quality; Europe; Regional labour markets